سیرت النبی ﷺ کی روشنی میں ہماری معاشرتی ذمہ داریاں: Our Social Responsibilities in the Light of Prophet’s Seerah - Dr.Noor Hayat Khan; Dr. Alam Khan (MEI, 2023)
This study thoroughly explores the profound significance of Prophet Muhammad's Seerah as a timeless guide for understanding and fulfilling contemporary social responsibilities. It employs a multidisciplinary approach to delve into various aspects of the Prophet's life, including his character and ethical principles. The Seerah emphasizes crucial values like compassion, justice, inclusivity, and empathy, essential for harmonious social relationships. It draws wisdom from the Prophet's interactions with diverse communities, commitment to addressing social inequalities, and roles as a mediator and statesman to offer insights for tackling modern challenges. The study also highlights the importance of education and moral development inspired by the Prophet's teachings and discusses the Seerah's relevance in promoting environmental sustainability and responsible citizenship. Ultimately, a deeper understanding of the Seerah can enhance individuals' and communities' commitment to contemporary social responsibilities, fostering a just and compassionate world.